A proposed method for world weightlifting championships team selection - Chiu, L. Z. F. (The Journal of Strength and Conditioning Research, 2009)
The caliber of competitors at the World Weightlifting Championships (WWC) has increased greatly over the past 20 years. As the WWC are the primary qualifiers for Olympic slots (1996 to present), it is imperative for a nation to select team members who will finish with a high placing and score team points. Previous selection methods were based on a simple percentage system. Analysis of the results from the 2006 and 2007 WWC indicates a curvilinear trend in each weight class, suggesting a simple percentage system will not maximize the number of team points earned. To maximize team points, weightlifters should be selected based on their potential to finish in the top 25. A 5-tier ranking system is proposed that should ensure the athletes with the greatest potential to score team points are selected.